2011
DOI: 10.1016/j.msea.2010.09.097
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and enhanced mechanical properties of an Mg–10Gd–2Y–0.5Zr alloy processed by cyclic extrusion and compression

Abstract: The evolution of microstructure and texture of an extruded GW102K Mg alloy processed by cyclic extrusion and compression (CEC) at 450 °C were investigated. Tensile tests were performed at room temperature and strain rate 5 × 10 −3 s −1 . The results show that the microstructure was effectively refined, and the initial fiber texture became disintegrated and developed a new texture after 14 CEC passes. It was found that the strength and ductility were simultaneously increased as compared with the as-extruded all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 24 publications
(30 reference statements)
1
19
0
Order By: Relevance
“…4 and 3d it can be seen that the second phase particles precipitate mainly along the DRX grain boundaries and only exist in the DRX zone, the mean diameter of the particles is larger than that reported in Refs. [25,26]. This may be ascribed to high contents of RE elements in the alloy.…”
Section: Microstructural Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 and 3d it can be seen that the second phase particles precipitate mainly along the DRX grain boundaries and only exist in the DRX zone, the mean diameter of the particles is larger than that reported in Refs. [25,26]. This may be ascribed to high contents of RE elements in the alloy.…”
Section: Microstructural Evolutionmentioning
confidence: 99%
“…This difference could be attributed to dynamic precipitation. The second phase particles precipitate along the DRX grain boundaries and had a strong ability to prevent the grains from rotating during the following straining [37]. Due to the cooperative effect of the dynamic recrystallization and dynamic precipitation, the final texture is weakened.…”
Section: Texture Analysesmentioning
confidence: 99%
“…High yield strength, 330 MPa, is obtained by introducing friction stir processing (FSP) into Mg-10Gd-3Y-0.5Zr cast [5]. Peng et al [6] reported that cyclic extrusion and compression (CEC) at 450 • C can refine the microstructure of GW102K Mg alloy. Precipitation strengthening is another attractive topic due to the large solid solution of Mg-RE alloys.…”
Section: Introductionmentioning
confidence: 99%
“…(2) elongation of the alloys increased obviously; (3) basal texture weakening to some extent; (4) microstructure distribution especially the secondary phase precipitates become more homogeneous; (5) yield strength of most alloys decreased, a few alloys have also increased, such as Mg-10Gd-2Y-0.5Zr as reported by [17].…”
Section: Introductionmentioning
confidence: 74%